Memetakan Hubungan antara Harga Diskon, Kualitas Produk, dan Niat Membeli Secara Impulsif melalui e-Commerce - Wanda, Meisya; Pasaribu, Pananda (APPS Publications, 2022)
The study aimed to analyze the relationships between price discounts, impulsive purchasing behavior, and perceived quality. This study collected primary data from respondents via questionnaires. Using the Smart PLS tools, this study uses the t-test and data regression to validate the hypothesis. The perceived quality factor performed an essential mediating effect in the relationship between price discounts and impulsive buying. When the direct effect of price discounts on impulsive buying was investigated, it was discovered that price discounts have no effect on people’s impulsive purchase. However, when perceived quality served as a mediator, the feelings created by a price discount led to a positive perception of product and give significant impact on impulsive buying behavior.